2008
DOI: 10.1063/1.2896577
|View full text |Cite
|
Sign up to set email alerts
|

Double planar wire array as a compact plasma radiation source

Abstract: Magnetically compressed plasmas initiated by a double planar wire array (DPWA) are efficient radiation sources. The two rows in a DPWA implode independently and then merge together at stagnation producing soft x-ray yields and powers of up to 11.5kJ∕cm and more than 0.4TW∕cm, higher than other planar arrays or low wire-number cylindrical arrays on the 1MA Zebra generator. DPWA, where precursors form in two stages, produce a shaped radiation pulse and radiate more energy in the main burst than estimates of impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 15 publications
3
45
0
Order By: Relevance
“…Saturn short pulse experiments at 5-6 MA could establish the scaling of x-ray power and yield up to current levels relevant for a multi-pinch vacuum hohlraum on Z using this alternate load geometry. Double planar arrays also may be better suited to fulfilling ICF pulse shaping requirements than single planar arrays [54].…”
Section: Chapter 4 Conclusion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saturn short pulse experiments at 5-6 MA could establish the scaling of x-ray power and yield up to current levels relevant for a multi-pinch vacuum hohlraum on Z using this alternate load geometry. Double planar arrays also may be better suited to fulfilling ICF pulse shaping requirements than single planar arrays [54].…”
Section: Chapter 4 Conclusion and Future Directionsmentioning
confidence: 99%
“…Perhaps higher wire number planar arrays would produce narrower pulses and higher x-ray powers more attractive for driving a hohlraum. It could also be worth studying double planar wire arrays on Saturn, in which two parallel linear arrays of wires are placed in close proximity [54]. Work on Zebra indicate they may scale more favorably than single planar arrays [35].…”
Section: Chapter 4 Conclusion and Future Directionsmentioning
confidence: 99%
“…Since that time numerous experiments have demonstrated that among all the other low-wirenumber loads the planar wire arrays yield the highest x-ray radiation energies and powers [9][10][11]. Two years later, the single planar array loads have been successfully tested at 3 − 5 MA currents on Saturn generator at SNL [5,13,14].…”
mentioning
confidence: 99%
“…[23], has been performed on principle of adding thin current filaments to describe the momentum redistribution to plasmas ablated from the array wires. Later this approach has been justified by the successful application of the WADM to the simulation of single and nested cylindrical arrays [24] and single-and double-planar arrays [11,25,26].…”
mentioning
confidence: 99%
See 1 more Smart Citation